The Influence of Electronic Word of Mouth and Digital Marketing on Decisions to Purchase Hotel Tickets Through Traveloka Applications (Case Study of Consumers in the City of Bandung) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This study aims to determine and analyze the effect of electronic Word of Mouth (e-WOM) and Digital Marketing on the decision to purchase hotel tickets through the Traveloka application. This research was conducted with a quantitative approach. Primary data collection was carried out by distributing questionnaires to a sample of 100 customers in the city of Bandung, and. The data analysis used in this study is a multiple linear regression test. The results showed that partially e-WOM and Digital Marketing had a positive and significant influence on purchasing decisions, e-WOM with a significance level of trust of 0.003